Hollow CoNiS polyhedrons/MnCoNi layered double hydroxide nanorod arrays on nickel foam as integral electrodes for improved oxygen evolution reaction in alkaline media. Issue 4 (22nd April 2022) - Shi, Huafeng; Ni, Yonghong
Abstract: The oxygen evolution reaction (OER) with sluggish kinetics in electron transportation has been the key process to develop water splitting technology for the hydrogen production. Here, we successfully prepared hollow CoNiS polyhedrons/MnCoNi layered double hydroxide (MCN LDH) nanorod arrays on Ni foam (labeled as CNS/MCN LDH/NF) through a two‐step wet chemical route, employing NF‐supported MCN LDH nanoneedle arrays as the substrate. ZIF‐67 polyhedrons first loaded on MCN LDH to form ZIF‐67/MCN LDH/NF, and then ZIF‐67/MCN LDH/NF was sulfurized to obtain the final product. The investigations revealed that MCN LDH could not be sulfurized under the current sulfurization conditions and simultaneously nickel element entered the sulfurized product to form hollow CoNiS polyhedrons. Electrochemical tests showed that the as‐obtained CNS/MCN LDH/NF electrode merely required 259 mV of overpotential in 1.0 M KOH solution to deliver the current density of 50 mA cm −2, which was lower than 372 mV of the hollow Co9 S8 polyhedrons/NF electrode. Furthermore, the as‐constructed CNS/MCN LDH/NF electrode could continuously and stably work at the current density of 100 mA cm −2 for 110 h, indicating its superb long‐term stability.